Heat treatment process of high-strength bolt
Patent Information
- Application Number
- CN202511819295.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-12-04
- Publication Date
- 2026-09-04
- Estimated Expiration
- 2045-12-04
AI Technical Summary
[0005]本发明提出一种高强度螺栓的热处理工艺,解决了相关技术中螺栓力学性能较差的问题
本发明中,通过优化螺栓坯材的组成成分,增强了螺栓坯材内部的结构稳定性,使其具有良好的力学性能,其中,通过在螺栓坯材中引入Mg、Eu、Se这三种元素,其中,Mg会偏聚在晶界处,使得晶粒达到细化的作用,细化的晶粒增加了晶界面积,可对螺栓坯材内部组织的位错运动造成阻碍;Eu能够与体系中C、N等间隙原子结合,形成在螺栓坯材基体中弥散分布的析出相,在一定程度上产生沉淀强化效果;Se的加入可减少杂质元素在晶界的偏聚,起到净化晶界的作用;因此通过Mg、Eu、Se这三种元素的并用,利用三者的互补组合,显著提高了螺栓的抗拉强度,使抗拉强度提高至1633MPa以上。
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] This invention relates to the field of bolt technology, and more specifically, to a heat treatment process for high-strength bolts. Background Technology
[0002] Bolts, as an important mechanical fastener, are widely used in key fields such as aerospace, automobile manufacturing, heavy machinery, and building structures. With the increasing demands of modern industry for equipment safety, reliability, and lightweighting, higher requirements are being placed on the mechanical properties of bolts, especially their tensile strength.
[0003] Currently, most high-strength bolts are made of medium-carbon alloy steel or low-alloy steel, and their strength is improved through quenching and tempering heat treatment. However, traditional heat treatment processes often have problems such as uneven microstructure, coarse grains, and internal stress concentration, which can lead to defects such as early fracture and low fatigue life in actual use.
[0004] Therefore, improving the mechanical properties of bolts is of great significance for extending their service life. Summary of the Invention
[0005] This invention proposes a heat treatment process for high-strength bolts, which solves the problem of poor mechanical properties of bolts in related technologies.
[0006] The technical solution of the present invention is as follows: This invention proposes a heat treatment process for high-strength bolts, comprising the following steps: High-strength bolts are obtained by vacuum quenching, tempering, and cooling of bolt blanks; The bolt blank is composed of the following components by weight percentage: C 0.1%~0.15%, Mn 0.4%~0.6%, Mo 0.25%~0.35%, W 0.05%~0.15%, Ti 0.2%~0.3%, Co 0.15%~0.25%, Yb 0.05%~0.1%, Mg 0.15%~0.25%, V 0.08%~0.12%, Eu 0.05%~0.15%, Se 0.03%~0.06%, with the balance being Fe and other unavoidable impurities.
[0007] As a further technical solution, the sum of the weight percentages of Mg, Eu, and Se is: 0.3% ≤ Mg + Eu + Se ≤ 0.4%.
[0008] In this invention, by optimizing the content ratio of Mg, Eu and Se, when the sum of the weight percentages of Mg, Eu and Se is 0.3%≤Mg+Eu+Se≤0.4%, the tensile strength of the bolt can be further improved.
[0009] As a further technical solution, the method for preparing the bolt blank includes the following steps: A1. Weigh the materials according to the weight percentage of the bolt blank, mix, melt, cast, and shape to obtain a bolt blank; A2. The bolt blank is obtained by drawing, cold heading, and thread processing.
[0010] As a further technical solution, the vacuum quenching is a first-stage vacuum quenching, a second-stage vacuum quenching, and a third-stage vacuum quenching; During the first stage of vacuum air quenching, the temperature is held at 950~1000℃ for 20~25min, and then cooled to 750~800℃ at a pressure of 1~6bar. During the second stage of vacuum quenching, the temperature is cooled to 400-450°C at a pressure of 12-14 bar. During the third stage of vacuum air quenching, the temperature is cooled to 200-250°C at a pressure of 1-6 bar, and then air-cooled to room temperature.
[0011] In this invention, the bolt blank undergoes vacuum quenching, tempering, and cooling treatment. The vacuum quenching is segmented. In the first segment, a gas pressure of 1-6 bar is used for cooling, allowing the bolt blank to cool from a high temperature of 950-1000℃ to 750-800℃ at a relatively slow rate. This avoids abnormal grain growth within the bolt blank caused by excessively rapid cooling. Subsequently, a gas pressure of 12-14 bar is used to appropriately accelerate the cooling rate, increasing the hardness of the bolt blank at this stage and providing basic strength support for the bolt. The cooling pressure is then reduced again, decreasing the cooling rate and reducing structural stress, resulting in a more uniform microstructure in the bolt blank. By adjusting the cooling gas pressure and cooling rate during the three segments of vacuum quenching, the internal microstructure of the bolt blank becomes more uniform, thus giving the bolt blank excellent wear resistance.
[0012] As a further technical solution, the pressure during the first stage of vacuum quenching is greater than the pressure during the third stage of vacuum quenching.
[0013] In this invention, when the pressure during the first stage of vacuum quenching is greater than the pressure during the third stage of vacuum quenching, the wear resistance of the bolt can be further improved.
[0014] As a further technical solution, nitrogen gas is independently introduced into the first stage vacuum quenching, the second stage vacuum quenching, and the third stage vacuum quenching.
[0015] As a further technical solution, during the tempering process, the temperature is increased to 500-550℃ at a heating rate of 80-100℃ / h, and then held for 2-4 hours.
[0016] As a further technical solution, the cooling process involves air cooling to room temperature.
[0017] As a further technical solution, the vacuum air quenching process also includes pretreatment; The specific steps of the pretreatment are as follows: after preheating the bolt blank, a solution treatment is performed.
[0018] As a further technical solution, during the pretreatment, the temperature is increased to 840-880℃ at a heating rate of 110-120℃ / h, and held for 30-40 minutes. During the solution treatment, the temperature is increased to 950-1000℃ at a heating rate of 80-90℃ / h, and held for 20-25 minutes.
[0019] The working principle and beneficial effects of this invention are as follows: In this invention, by optimizing the composition of the bolt blank, the internal structural stability of the bolt blank is enhanced, giving it excellent mechanical properties. Specifically, by introducing three elements—Mg, Eu, and Se—into the bolt blank, Mg segregates at grain boundaries, refining the grains. The refined grains increase the grain boundary area, which can hinder dislocation movement within the bolt blank. Eu can combine with interstitial atoms such as C and N in the system to form precipitates that are dispersed in the bolt blank matrix, producing a precipitation strengthening effect to a certain extent. The addition of Se can reduce the segregation of impurity elements at grain boundaries, thus purifying the grain boundaries. Therefore, by using Mg, Eu, and Se in combination, and utilizing their complementary combination, the tensile strength of the bolt is significantly improved, increasing it to over 1633 MPa. Detailed Implementation
[0020] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.
[0021] Example 1 The bolt blank consists of the following components by weight percentage: C 0.1%, Mn 0.4%, Mo 0.25%, W 0.05%, Ti 0.2%, Co 0.15%, Yb 0.05%, Mg 0.15%, V 0.08%, Eu 0.05%, Se 0.03%, with the balance being Fe and other unavoidable impurities; The method for preparing bolt blanks includes the following steps: A1. Weigh the components according to the weight percentage of the bolt blank, mix, melt, cast, and shape to obtain the bolt blank; A2. After drawing, cold heading, and thread processing of the bolt blank, the bolt blank material is obtained. A heat treatment process for high-strength bolts includes the following steps: The bolt blank was heated to 840℃ at a heating rate of 110℃ / h and held for 40 min. Then, it was heated to 950℃ at a heating rate of 80℃ / h and held for 25 min. Nitrogen gas was introduced for vacuum quenching. The blank was then cooled to 750℃ at 1 bar pressure. The nitrogen pressure was adjusted and the blank was cooled to 400℃ at 12 bar pressure. The blank was then cooled to 200℃ at 1 bar nitrogen pressure and air-cooled to room temperature to complete the vacuum quenching. Finally, the blank was heated to 500℃ at a heating rate of 80℃ / h and held for 4 h. The blank was then air-cooled to room temperature to obtain a high-strength bolt.
[0022] Example 2 The bolt blank consists of the following components by weight percentage: C 0.13%, Mn 0.5%, Mo 0.3%, W 0.1%, Ti 0.25%, Co 0.2%, Yb 0.08%, Mg 0.18%, V 0.1%, Eu 0.08%, Se 0.04%, with the balance being Fe and other unavoidable impurities; The method for preparing bolt blanks includes the following steps: A1. Weigh the components according to the weight percentage of the bolt blank, mix, melt, cast, and shape to obtain the bolt blank; A2. After drawing, cold heading, and thread processing, the bolt blank is obtained. A heat treatment process for high-strength bolts includes the following steps: The bolt blank was heated to 860℃ at a heating rate of 115℃ / h and held for 35 min. Then, it was heated to 980℃ at a heating rate of 85℃ / h and held for 20 min. Nitrogen gas was introduced for vacuum quenching. The blank was then cooled to 780℃ at a pressure of 4 bar. The nitrogen pressure was adjusted and the blank was cooled to 430℃ at a pressure of 13 bar. The blank was then cooled to 230℃ at a nitrogen pressure of 4 bar and air-cooled to room temperature to complete the vacuum quenching. Finally, the blank was heated to 530℃ at a heating rate of 90℃ / h and held for 3 h. The blank was then air-cooled to room temperature to obtain a high-strength bolt.
[0023] Example 3 The bolt blank consists of the following components by weight percentage: C 0.15%, Mn 0.6%, Mo 0.35%, W 0.15%, Ti 0.3%, Co 0.25%, Yb 0.1%, Mg 0.25%, V 0.12%, Eu 0.15%, Se 0.06%, with the balance being Fe and other unavoidable impurities; The method for preparing bolt blanks includes the following steps: A1. Weigh the components according to the weight percentage of the bolt blank, mix, melt, cast, and shape to obtain the bolt blank; A2. After drawing, cold heading, and thread processing, the bolt blank is obtained. A heat treatment process for high-strength bolts includes the following steps: The bolt blank was heated to 880℃ at a heating rate of 120℃ / h and held for 30 min. Then, it was heated to 1000℃ at a heating rate of 90℃ / h and held for 20 min. Nitrogen gas was then introduced for vacuum quenching. The blank was cooled to 800℃ at a pressure of 6 bar. The nitrogen pressure was adjusted and the blank was cooled to 450℃ at a pressure of 14 bar. The blank was then cooled to 250℃ at a nitrogen pressure of 6 bar and air-cooled to room temperature to complete the vacuum quenching. The blank was then heated to 550℃ at a heating rate of 100℃ / h and held for 4 h. Finally, the blank was air-cooled to room temperature to obtain a high-strength bolt.
[0024] Example 4 The only difference between this embodiment and Embodiment 2 is that the weight percentage of Mg in the bolt blank in this embodiment is 0.21%, the weight percentage of Eu is 0.12%, and the weight percentage of Se is 0.04%.
[0025] Example 5 The only difference between this embodiment and Embodiment 2 is that the weight percentage of Mg in the bolt blank in this embodiment is 0.23%, the weight percentage of Eu is 0.12%, and the weight percentage of Se is 0.05%.
[0026] Example 6 The only difference between this embodiment and Embodiment 5 is that the heat treatment process for the high-strength bolts in this embodiment is different, specifically: The bolt blank was heated to 860℃ at a heating rate of 115℃ / h and held for 35 minutes. Then, it was heated to 980℃ at a heating rate of 85℃ / h and held for 20 minutes. Nitrogen gas was introduced for vacuum quenching. The blank was then cooled to 780℃ at a pressure of 2 bar. The nitrogen pressure was adjusted and the blank was cooled to 430℃ at a pressure of 13 bar. The blank was then cooled to 230℃ at a nitrogen pressure of 6 bar and air-cooled to room temperature to complete the vacuum quenching. Finally, the blank was heated to 530℃ at a heating rate of 90℃ / h and held for 3 hours. The blank was then air-cooled to room temperature to obtain a high-strength bolt.
[0027] Example 7 The only difference between this embodiment and Embodiment 5 is that the heat treatment process for the high-strength bolts in this embodiment is different, specifically: The bolt blank was heated to 860℃ at a heating rate of 115℃ / h and held for 35 minutes. Then, it was heated to 980℃ at a heating rate of 85℃ / h and held for 20 minutes. Nitrogen gas was introduced for vacuum quenching. The blank was then cooled to 780℃ at a pressure of 6 bar. The nitrogen pressure was adjusted and the blank was cooled to 430℃ at a pressure of 13 bar. The blank was then cooled to 230℃ at a nitrogen pressure of 2 bar and air-cooled to room temperature to complete the vacuum quenching. Finally, the blank was heated to 530℃ at a heating rate of 90℃ / h and held for 3 hours. The blank was then air-cooled to room temperature to obtain a high-strength bolt.
[0028] Example 8 The only difference from Example 5 is that the heat treatment process for the high-strength bolts in this example is different, specifically: The bolt blank was heated to 860℃ at a heating rate of 115℃ / h and held for 35 min. Then, it was heated to 980℃ at a heating rate of 85℃ / h and held for 20 min. Nitrogen gas was introduced for vacuum quenching. The blank was then cooled to 430℃ at a pressure of 13 bar and then cooled to 230℃ at a nitrogen pressure of 4 bar. After air cooling to room temperature, the blank was completed. Finally, it was heated to 530℃ at a heating rate of 90℃ / h and held for 3 h. After air cooling to room temperature, a high-strength bolt was obtained.
[0029] Example 9 The only difference from Example 5 is that the heat treatment process for the high-strength bolts in this example is different, specifically: The bolt blank was heated to 860℃ at a heating rate of 115℃ / h and held for 35 minutes. Then, it was heated to 980℃ at a heating rate of 85℃ / h and held for 20 minutes. Nitrogen gas was introduced for vacuum quenching. The blank was then cooled to 780℃ at a pressure of 4 bar. The nitrogen pressure was adjusted, and the blank was cooled to 230℃ at a pressure of 13 bar. The blank was then air-cooled to room temperature to complete the vacuum quenching. Finally, the blank was heated to 530℃ at a heating rate of 90℃ / h and held for 3 hours. The blank was then air-cooled to room temperature to obtain a high-strength bolt.
[0030] Example 10 The only difference from Example 5 is that the heat treatment process for the high-strength bolts in this example is different, specifically: The bolt blank was heated to 860℃ at a heating rate of 115℃ / h and held for 35 minutes. Then, it was heated to 980℃ at a heating rate of 85℃ / h and held for 20 minutes. Nitrogen gas was introduced for vacuum quenching. The blank was then cooled to 230℃ under a pressure of 4 bar and air-cooled to room temperature to complete the vacuum quenching. After that, the blank was heated to 530℃ at a heating rate of 90℃ / h and held for 3 hours. Finally, it was air-cooled to room temperature to obtain a high-strength bolt.
[0031] Example 11 The only difference from Example 5 is that the heat treatment process for the high-strength bolts in this example is different, specifically: The bolt blank was heated to 860℃ at a heating rate of 115℃ / h and held for 35 minutes. Then, it was heated to 980℃ at a heating rate of 85℃ / h and held for 20 minutes. Nitrogen gas was introduced for vacuum quenching. The blank was then cooled to 230℃ at a pressure of 13 bar and air-cooled to room temperature to complete the vacuum quenching. After that, the blank was heated to 530℃ at a heating rate of 90℃ / h and held for 3 hours. Finally, it was air-cooled to room temperature to obtain a high-strength bolt.
[0032] Comparative Example 1 The only difference between this comparative example and Example 2 is that the weight percentage of Mg in the bolt blank of this comparative example is 0.3%, and Eu and Se are not added.
[0033] Comparative Example 2 The only difference between this comparative example and Example 2 is that the weight percentage of Eu in the bolt blank of this comparative example is 0.3%, and Mg and Se are not added.
[0034] Comparative Example 3 The only difference between this comparative example and Example 2 is that the weight percentage of Se in the bolt blank of this comparative example is 0.3%, and Mg and Eu are not added.
[0035] Comparative Example 4 The only difference between this comparative example and Example 2 is that in the bolt blank of this comparative example, Mg is replaced with an equal amount of Al.
[0036] Comparative Example 5 The only difference between this comparative example and Example 2 is that Eu is replaced with an equal amount of Tb in the bolt blank of this comparative example.
[0037] Comparative Example 6 The only difference between this comparative example and Example 2 is that in the bolt blank of this comparative example, Se is replaced with an equal amount of Tb.
[0038] Comparative Example 7 The only difference between this comparative example and Example 2 is that Mg, Eu, and Se were not added to the bolt blank in this comparative example.
[0039] Experimental Example 1 The high-strength bolts prepared in Examples 1-5 and Comparative Examples 1-7 were tested for tensile strength according to the test methods in GB / T 228.1-2021 "Metallic materials, tensile testing—Part 1: Test at room temperature," with a test speed of 0.006 s for all samples. -1 The test results for each group are the average values of 5 samples, and the test results are shown in Table 1. Table 1 Performance test results of Examples 1-5 and Comparative Examples 1-7
[0040] Compared with Comparative Examples 1-7, the bolts prepared in Examples 1-5 showed improved tensile strength, indicating that the combined use of Mg, Eu, and Se in the bolt blank can effectively improve the mechanical properties of the bolt, increasing its tensile strength to over 1633 MPa.
[0041] Experimental Example 2 The high-strength bolts prepared in Examples 5-11 were subjected to high-temperature friction and wear tests using a wear testing machine. The wear volume at 600℃ was measured, and the test results are shown in Table 2.
[0042] Table 2 Performance test results of Examples 5-11
[0043] Compared with Examples 8-11, the wear volume of the high-strength bolts prepared in Examples 5-7 was significantly reduced. This indicates that when the bolt blank is subjected to vacuum quenching, it is divided into three stages: first stage vacuum quenching, second stage vacuum quenching, and third stage vacuum quenching. By adjusting the gas pressure of each stage of vacuum quenching, the bolt blank can have a suitable cooling rate during the vacuum quenching process, which can make the bolt blank have a stable microstructure and improve the wear resistance of the bolt.
[0044] Compared with Examples 5 and 6, the wear volume of the high-strength bolt in Example 7 is significantly reduced, indicating that when the pressure during the first stage of vacuum quenching is greater than the pressure during the third stage of vacuum quenching, the wear resistance of the bolt can be further improved.
[0045] The above are merely preferred embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.
Claims
1. A heat treatment process for high-strength bolts, characterized in that, Includes the following steps: High-strength bolts are obtained by vacuum quenching, tempering, and cooling of bolt blanks; The bolt blank is composed of the following components by weight percentage: C 0.1%~0.15%, Mn 0.4%~0.6%, Mo 0.25%~0.35%, W 0.05%~0.15%, Ti 0.2%~0.3%, Co 0.15%~0.25%, Yb 0.05%~0.1%, Mg 0.15%~0.25%, V 0.08%~0.12%, Eu 0.05%~0.15%, Se 0.03%~0.06%, with the balance being Fe and other unavoidable impurities; The method for preparing the bolt blank includes the following steps: A1. Weigh the materials according to the weight percentage of the bolt blank, mix, melt, cast, and shape to obtain a bolt blank; A2. The bolt blank is obtained by drawing, cold heading, and thread processing.
2. The heat treatment process for a high-strength bolt according to claim 1, characterized in that, The sum of the weight percentages of Mg, Eu, and Se is: 0.3% ≤ Mg + Eu + Se ≤ 0.4%.
3. The heat treatment process for a high-strength bolt according to claim 1, characterized in that, The vacuum quenching consists of a first stage vacuum quenching, a second stage vacuum quenching, and a third stage vacuum quenching. During the first stage of vacuum air quenching, the temperature is held at 950~1000℃ for 20~25min, and then cooled to 750~800℃ at a pressure of 1~6bar. During the second stage of vacuum quenching, the temperature is cooled to 400-450°C at a pressure of 12-14 bar. During the third stage of vacuum air quenching, the temperature is cooled to 200-250°C at a pressure of 1-6 bar, and then air-cooled to room temperature.
4. The heat treatment process for a high-strength bolt according to claim 3, characterized in that, The pressure during the first stage of vacuum quenching is greater than the pressure during the third stage of vacuum quenching.
5. The heat treatment process for a high-strength bolt according to claim 3, characterized in that, Nitrogen gas is introduced independently into the first stage of vacuum quenching, the second stage of vacuum quenching, and the third stage of vacuum quenching.
6. The heat treatment process for a high-strength bolt according to claim 1, characterized in that, During the tempering process, the temperature is increased to 500-550℃ at a heating rate of 80-100℃ / h, and then held for 2-4 hours.
7. The heat treatment process for a high-strength bolt according to claim 1, characterized in that, During the cooling process, the air is used to cool the material to room temperature.
8. The heat treatment process for a high-strength bolt according to claim 1, characterized in that, The vacuum air quenching process also includes pretreatment. The specific steps of the pretreatment are as follows: after preheating the bolt blank, a solution treatment is performed.
9. The heat treatment process for a high-strength bolt according to claim 8, characterized in that, During the preheating treatment, the temperature is increased to 840-880℃ at a heating rate of 110-120℃ / h, and held for 30-40 minutes. During the solution treatment, the temperature is increased to 950-1000℃ at a heating rate of 80-90℃ / h, and held for 20-25 minutes.
Citation Information
Patent Citations
1400MPa grade delayed-fracture-resistant high-strength bolt and manufacturing method
CN110468341A
High-strength nut and preparation process thereof
CN120536834A